Respostas
respondido por:
2
(x-1)+(x)+(x+1)=393
3x-1+1=393
3x=393
x=131
131-1=130
x+1=132
130+131+132=393
3x-1+1=393
3x=393
x=131
131-1=130
x+1=132
130+131+132=393
respondido por:
3
Como não sabemos que número é , iremos chamá-lo de ''x''.
▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃
x + x+1 + x+2 = 393
3x + 3 =393
3x = 393 - 3
3x = 390
x = 390/3
x = 130
▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃
Portanto os números são : 130 , 131 e 132.
▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃▃
Espero ter ajudado!
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás